2020
DOI: 10.1002/acm2.12797
|View full text |Cite
|
Sign up to set email alerts
|

The use of 0.5rcav as an effective point of measurement for cylindrical chambers may result in a systematic shift of electron percentage depth doses

Abstract: Electron dosimetry can be performed using cylindrical chambers, plane-parallel chambers, and diode detectors. The finite volume of these detectors results in a displacement effect which is taken into account using an effective point of measurement (EPOM). Dosimetry protocols have recommended a shift of 0.5 r cav for cylindrical chambers; however, various studies have shown that the optimal shift may deviate from this recommended value. This study investigated the effect that the selection of EPOM shift for cyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…10-12 Monte Carlo simulations have shown that, depending on the method of EPOM determination, 0.5rcyl shift is correct or is too large, resulting in a systematic error 13,14 of ionization chamber readings. The smaller is the size of a thimble chamber, the smaller should be ∆z the shift of EPOM 10, 14 . However, for plane-parallel chambers, the lower was the electron beam energy, the larger EPOM shift was observed, as reported in 13, 15 .…”
Section: Introductionmentioning
confidence: 99%
“…10-12 Monte Carlo simulations have shown that, depending on the method of EPOM determination, 0.5rcyl shift is correct or is too large, resulting in a systematic error 13,14 of ionization chamber readings. The smaller is the size of a thimble chamber, the smaller should be ∆z the shift of EPOM 10, 14 . However, for plane-parallel chambers, the lower was the electron beam energy, the larger EPOM shift was observed, as reported in 13, 15 .…”
Section: Introductionmentioning
confidence: 99%